“No hermano mío, no me hagas violencia…”: Lectura de 2º Samuel 13:1-22 (Theological Kronos, 2019)
This article studies the Tamar´s story, this story is in 2nd Samuel 13:1-22. Which relates the Tamar´s life, a virginity woman that was cheated, abused and forgotten for two of her brothers, for her father, David king and for the Amnon´s slave, her brother. This written has the objectives to show the reader than, inside the biblical text, exist the stories that denigrate the woman. And also illustrating to the reader, the God´s voice of protest through Tamar, the voice against the patriarchal system that minimizes the woman´s voice and forgotten what has done. This article proposes the exegetic method “Sociosymbolic”, applied to the gender perspective in the patriarchal machista system of the actual society
Keywords: Woman; Violence; Patriarchal system; Virginity; Forgetfulness; Protest